2003
DOI: 10.1016/s0997-7546(03)00049-9
|View full text |Cite
|
Sign up to set email alerts
|

On the breaking of long, axisymmetric liquid bridges between unequal supporting disks at minimum volume stability limit

Abstract: The stability of axisymmetric liquid bridges held between non-equal circular supporting disks, and subjected to an axial acceleration, has been analyzed both theoretically and experimentally. Some characteristics of the breaking process which takes place when the stability limit of minimum volume is reached (mainly the dependence with the disks separation of the volume of the liquid drops resulting after the liquid bridge breakage) have been theoretically studied by using standard asymptotic expansion techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…20,21 However, the accuracy of the surface tension obtained from a sessile drop was far below the accuracy that can be obtained from a pendant drop: 1.0 mJ/m 2 accuracy at best using sessile drops versus 0.01 mJ/m 2 accuracy using pendant drops. 17 Recently, a new version of ADSA called ADSA-no apex (ADSA-NA) was developed 22 that extends the applicability of the ADSA methodology to configurations without an apex (e.g., liquid bridges 23,24 ). ADSA-NA does not require information about the apex region and was developed primarily for contact angle measurement using sessile drops with a capillary protruding into the drop.…”
Section: ' Introductionmentioning
confidence: 99%
“…20,21 However, the accuracy of the surface tension obtained from a sessile drop was far below the accuracy that can be obtained from a pendant drop: 1.0 mJ/m 2 accuracy at best using sessile drops versus 0.01 mJ/m 2 accuracy using pendant drops. 17 Recently, a new version of ADSA called ADSA-no apex (ADSA-NA) was developed 22 that extends the applicability of the ADSA methodology to configurations without an apex (e.g., liquid bridges 23,24 ). ADSA-NA does not require information about the apex region and was developed primarily for contact angle measurement using sessile drops with a capillary protruding into the drop.…”
Section: ' Introductionmentioning
confidence: 99%
“…As indicated in Table 1 these experiments deal mainly with liquid bridges between coaxial disks of the same diameter, and they have been oriented to the study of the equilibrium shapes and stability of liquid bridges subject to both axial [4,22,23] and lateral accelerations [24][25][26][27], to the analysis of the breaking dynamics [4,22], and to the analysis of thermal problems related to Marangoni flow [28] and the influence of a temperature gradient along the liquid column span on the stability of long liquid bridges [29].…”
Section: Milimetric Liquid Bridge Facilitymentioning
confidence: 99%
“…Concerning liquid bridges theoretical approach, a great effort has been done world wide in the last decades to determine equilibrium shapes and stability limits for a wide range of liquid bridge configurations (a review of the literature dealing with these effects can be found in [3,4]). Besides, numerous papers on liquid bridge dynamics have been also published.…”
Section: Introductionmentioning
confidence: 99%
“…These static stability limits were subsequently shown to be represented by a single closed piecewise curve on the slenderness/volume plane [59], and each set of dimensionless parameters (Λ, γ, B) defines a minimum volume where a stable liquid bridge can form, and three unstable modes. Numerous experimental and theoretical studies [60][61][62] have extended these analyses to account for contact angle, geometrical parameters, and surface energy effects as well as the influence of gravity and electrical fields. For example, DaRiva and Martinez [60] showed that the contact angle should not exceed π, or else the liquid bridge will spread over the surface, and Gomez et al [34] described analytically the effect of small axisymmetric imperfection on the behavior of liquid bridges supported by two circular, coaxial disks.…”
Section: Introductionmentioning
confidence: 99%